2013
DOI: 10.5005/jp-journals-10024-1391
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Anomalies in Saudi Orthodontic Patients

Abstract: Aim: This study aimed to investigate the prevalence of dental anomalies and study the association of these anomalies with different types of malocclusion in a random sample of Saudi orthodontic patients. Materials and methods:Six hundred and two randomly selected pretreatment records including orthopantomographs (OPG), and study models were evaluated. The molar relationship was determined using pretreatment study models, and OPG were examined to investigate the prevalence of dental anomalies among the sample. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
31
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 16 publications
(39 reference statements)
6
31
2
2
Order By: Relevance
“…These associations could affect orthodontic treatment planning. To date, no study has verified this association in Brazilian orthodontic patients, (3). Therefore, the aims of this study were to evaluate the prevalence of developmental dental anomalies in non-syndromic orthodontic patients and verify their association with different malocclusions.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…These associations could affect orthodontic treatment planning. To date, no study has verified this association in Brazilian orthodontic patients, (3). Therefore, the aims of this study were to evaluate the prevalence of developmental dental anomalies in non-syndromic orthodontic patients and verify their association with different malocclusions.…”
Section: Introductionmentioning
confidence: 95%
“…They exhibit several degrees of severity, from chronological delay in odontogenesis to complete absence of a tooth germ, also comprising deviations in morphology and position of the teeth in the arch (2). Orthodontic patients have higher rates of anomalies compared to the general population, which interfere greatly with the diagnosis and orthodontic treatment planning (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 A study with 602 randomly selected pre-treatment OPG records found that ST was among the most commonly registered dental anomalies. 26 A study was conducted at Ras Al Khaimmah, UAE, with 2925 panoramic radiographs from non-syndromic patients; it was found that paramolars and distomolars were registered (two cases for each ST) for each among 6.25%. 27 Hence, the aim of the present article was to report a case with a unilateral maxillary distomolar in a patient with multiple abnormalities and the possible treatment options and present a mini review on supernumerary distomolar teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Анализ распространенности и тяжести ЗЧА является важным этапом в процессе планирования профилактических и лечебных мероприятий [1,2]. Важно иметь представление о частоте встречаемости ЗЧА не только в стране, но и каждом отдельном регионе, поскольку эти данные могут значительно варьировать в зависимости от географической принадлежности [11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
unclassified